Think happy! - Carlson, Nancy L. (Minneapolis : Carolrhoda Books, 2009)
Colorful illustrations of animals and simple text encourage early readers to maintain positive thinking, and describe lots of things to do that can make a person happy.
2.8
K-3
Keywords: Conduct of life -- Juvenile literature; Happiness -- Juvenile literature; Conduct of life; Happiness; Conduct of life; Happiness